Pengaruh Edukasi Terhadap Kepatuhan Ibu Hamil Dalam Mengkonsumsi Tablet Fe Selama Kehamilan - Malinie, Hema; Yunita, Laurensia; Yuwindry, Iwan (Akademi Kebidanan Bunga Husada Samarinda, 2024)
Anemia in pregnant women is still a national problem because it reflects the value of the socio-economic welfare of the community, and has a very large influence on the quality of human resources. To find out the educational effect of consuming Fe tablets on the compliance of pregnant women in consuming Fe tablets during pregnancy at the Pekauman Health Center. This research is a quantitative type using a minimum sampling technique of 30 respondents with a pre-experimental design using RCT pretest-posttest. Data collection was carried out using the MMAS-8 questionnaire. Analysis of research data using univariate and bivariate analysis of marginal homogeneity to determine the frequency and percentage of each research variable. The results of the marginal homogeneity test obtained a p value equal to 0.000 where p less than 0.05 means that there is a difference between variables. These results state that there is an effect of Fe Tablet Consumption Education on the Compliance of Pregnant Women in Consuming Fe Tablets during Pregnancy at the Pekauman Health Center. The results of the intervention group adherence study after being given Fe Tablet Consumption Education on the Compliance of Pregnant Women in Consuming Fe Tablets During Pregnancy at the Pekauman Health Center, namely 13 people (86,7 percent) were categorized at the high adherence level and as many as 2 people (13,3 percent) were categorized at the low level of adherence. medium compliance.